Gamification for innovators and entrepreneurs : using games to drive innovation and facilitate learning - Henning, Breuer; Bessant, J. R.; Gudiksen, Sune (Business and economics., 2022)
Gamification for Innovators and Entrepreneurs is about an exciting, still emerging superpower. One that empowers you to use, repurpose and create games that will help solve the great societal and organisational challenges that companies, startups and nonprofits are facing today - games that are explicitly designed and can be iteratively improved to engage stakeholders, facilitate experimentation and actually drive innovation. What makes gamification a superpower is its use of powerful methods and techniques from diverse disciplines and traditions - like futures studies, user experience, agile management, design thinking or business design - in a new, action-oriented and engaging framework. Each game world is a safe, playful space, where groups are free to experiment in innovative and inclusive forms of collaboration. Gamification for Innovators and Entrepreneurs builds on insights and knowledge from over 150 leading experts in the field. It provides a rich collection of materials for innovators, entrepreneurs and game designers that allows you to dive deep into innovation and entrepreneurship, into games and gamification. You can build on 36 gamification design patterns - like dilemma solving, experiential learning, innovation markets and storytelling - and use a game design canvas to create your own innovation games. Or you can customize some of the 70+ games featured in the book that are already in use by innovators, entrepreneurs and professional trainers. Additional resources are provided for teachers and game facilitators. The superpower of gamification does not yield simplistic solutions - but the resources from Gamification for Innovators and Entrepreneurs will provide you with the means and the confidence to tackle some of the great challenges we are all facing today. An easily accessible and comprehensive overview on gamification and games in the context of innovation and entrepreneurship Draws on several collaborative research projects involving partners such as Lego, Deutsche Telekom, Lufthansa Systems, 3M, Danske Bank, and Nokia Systems. Extensive experience of the authors in the facilitation of games, their role as an enabler of learning and their potential to facilitate transformation. 36 reusable gamification design patterns, a five-step process and a game design canvas to create one's own innovation games Summaries and references of more than 70+ customizable games that are already in use by innovators, entrepreneurs and professional trainers Educational materials for teachers, trainers and game facilitators.